Examination of a pre-exercise, high energy supplement on exercise performance - Tranchina Christopher P; Hoffman Mattan W; Ratamess Nicholas A; Kang Jie; Hoffman Jay R; Faigenbaum Avery D (Taylor & Francis Group, 2009)
Abstract Background The purpose of this study was to examine the effect of a pre-exercise high energy drink on reaction time and anaerobic power in competitive strength/power athletes. In addition, the effect of the pre-exercise drink on subjective feelings of energy, fatigue, alertness and focus was also explored. Methods Twelve male strength/power athletes (21.1 ± 1.3 y; 179.8 ± 7.1 cm; 88.6 ± 12.1 kg; 17.6 ± 3.3% body fat) underwent two testing sessions administered in a randomized and double-blind fashion. During each session, subjects reported to the Human Performance Laboratory and were provided with either 120 ml of a high energy drink (SUP), commercially marketed as Redline Extreme® or 120 ml of a placebo (PL) that was similar in taste and appearance but contained no active ingredients. Following consumption of the supplement or placebo subjects rested quietly for 10-minutes prior to completing a survey and commencing exercise. The survey consisted of 4 questions asking each subject to describe their feelings of energy, fatigue, alertness and focus for that moment. Following the completion of the questionnaire subjects performed a 2-minute quickness and reaction test on the Makoto testing device (Makoto USA, Centennial CO) and a 20-second Wingate Anaerobic Power test. Following a 10-minute rest subjects repeated the testing sequence and after a similar rest period a third and final testing sequence was performed. The Makoto testing device consisted of subjects reacting to both a visual and auditory stimulus and striking one out of 30 potential targets on three towers. Results Significant difference in reaction performance was seen between SUP and PL in both average number of targets struck (55.8 ± 7.4 versus 51.9 ± 7.4, respectively) and percent of targets struck (71.9 ± 10.5% versus 66.8 ± 10.9%, respectively). No significant differences between trials were seen in any anaerobic power measure. Subjective feelings of energy (3.5 ± 0.5 versus 3.1 ± 0.5) and focus (3.8 ± 0.5 versus 3.3 ± 0.7) were significantly higher during SUP compared to PL, respectively. In addition, a trend towards an increase in average alertness (p = 0.06) was seen in SUP compared to P. Conclusion Results indicate a significant increase in reaction performance, with no effect on anaerobic power performance. In addition, ingestion of this supplement significantly improves subjective feelings of focus and energy in male strength/power athletes.